Effect of heterocycle content on metal binding isostere coordination. Issue 26 (24th June 2020) - Dick, Benjamin L.; Patel, Ashay; Cohen, Seth M.
Abstract : Bioisostere replacement is a core concept in modern medicinal chemistry and in this work new metal-binding isosteres (MBIs) are synthesized and evaluated for use in metalloenzyme inhibitors. Abstract : Bioisostere replacement is a core concept in modern medicinal chemistry and has proven an invaluable strategy to address pharmacodynamic and pharmacokinetic limitations of therapeutics. The success of bioisostere replacement is often dependent on the scaffold that is being modified ( i.e., "context dependence"). The application of bioisostere replacement to a picolinic acid fragment was recently demonstrated as a means to expand a library of metal-binding pharmacophores (MBPs) to modulate their physicochemical properties, while retaining their metal binding and metalloenzyme inhibitory activity. Here, metal binding isosteres (MBIs) with different nitrogen-containing heteroarenes is explored. This resulted in a number of new MBIs that were evaluated for their physicochemical properties and metal binding features. It was observed that the coordination behavior of an MBI is dependent on the identity and arrangement of the heteroatoms within each heteroarene. To further understand the observed coordination chemistry trends, density functional theory (DFT) calculations were performed. Theory indicates that preferences in coordination geometry are largely determined by the electronic character of the heteroarene scaffold. These results provide important insights into the development of novel MBI scaffolds that can serve to broaden the scope of scaffolds for metalloenzyme inhibitor development.